2012
DOI: 10.1007/82_2012_279
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Drug Resistance in Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) has become a curable disease thanks to the discovery of antibiotics. However, it has remained one of the most difficult infections to treat. Most current TB regimens consist of six to nine months of daily doses of four drugs that are highly toxic to patients. The purpose of these lengthy treatments is to completely eradicate Mycobacterium tuberculosis, notorious for its ability to resist most antibacterial agents, thereby preventing the formation of drug resistant mutants. On the contrary, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
172
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(177 citation statements)
references
References 133 publications
2
172
1
2
Order By: Relevance
“…Although the emergence of RIF/MXFresistant mutants from the RIF persistence phase cells in the present work was demonstrated using M. tuberculosis cells exposed to RIF in vitro, the identity of the mutations to those that were clinically relevant in TB patients the world over (52)(53)(54)(55)(56)(57)(58)(59)(76)(77)(78)(79)(80)(81)(82) indicated that the phenomenon of the emergence of RIF/MXF-resistant mutants from the RIF persistence phase might have been happening in vivo as well. Distinct from the previous studies, which showed emergence of genetically resistant Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa mutants upon short-duration exposure to sublethal concentrations of antibiotics (38)(39)(40)(41)(42), our study demonstrates that continuous prolonged exposure of M. tuberculosis cells to lethal concentrations of RIF causes de novo emergence of RIF-or MXF-resistant mutants from the RIF persistence phase cells at high frequency.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Although the emergence of RIF/MXFresistant mutants from the RIF persistence phase cells in the present work was demonstrated using M. tuberculosis cells exposed to RIF in vitro, the identity of the mutations to those that were clinically relevant in TB patients the world over (52)(53)(54)(55)(56)(57)(58)(59)(76)(77)(78)(79)(80)(81)(82) indicated that the phenomenon of the emergence of RIF/MXF-resistant mutants from the RIF persistence phase might have been happening in vivo as well. Distinct from the previous studies, which showed emergence of genetically resistant Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa mutants upon short-duration exposure to sublethal concentrations of antibiotics (38)(39)(40)(41)(42), our study demonstrates that continuous prolonged exposure of M. tuberculosis cells to lethal concentrations of RIF causes de novo emergence of RIF-or MXF-resistant mutants from the RIF persistence phase cells at high frequency.…”
Section: Discussioncontrasting
confidence: 91%
“…We did not attempt to select a combined RIF-MXF double resistant mutant from the RIF persistence phase cells due to the very low combined frequency (10 Ϫ4 ϫ 10 Ϫ4 ϭ 10 Ϫ8 ; mutation frequency of 10 Ϫ4 each for the RIF-and MXF-resistant mutants; see Results) of emergence of the mutant. It was speculated that once a persistence phase cell survives the killing action of ROS, the continued exposure to the same ROS could increase the opportunity to acquire mutations and gain resistance (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic factors are likely to be involved in the regulation of such transporter mechanisms but have not been extensively investigated in M tuberculosis. 243 Considerable progress has been made in understanding the mechanisms of resistance for most key first-line and second-line antituberculosis drugs, but further work is needed to identify the full range of mutations and to define their clinical efficacy. 244 Resistance to rifampicin is almost entirely due to changes in the β subunit of DNA-dependent RNA polymerase, which is encoded by the rpoB gene.…”
Section: Genotypic Testingmentioning
confidence: 99%
“…The majority of drug resistance in Mtb results from chromosomal mutations in genetic loci associated with the drug target, enzymes modifying the target or drug, or proteins needed for conversion of prodrugs to their active form [14]. Although numerous studies have contributed to the current understanding of the genetic basis of resistance in Mtb, most of these studies have examined a limited number of specific loci, and gaps in our knowledge remain, especially for correlating genotypic with phenotypic data [15][16][17].…”
Section: Need For a Tuberculosis Relational Sequencing Data Platformmentioning
confidence: 99%